EMX2OS serves as a biomarker of neonatal sepsis and participates acute lung injury through enhancing ferroptosis - Li, Xuexiang; Liu, Zhiqiang; Shan, Guilian; Shi, Lili; Liu, Zhihua (Frontiers in Pediatrics, 2025)
BackgroundNeonatal Sepsis (NS) is an important cause of neonatal death, often accompanied by acute lung injury (ALI). Ferroptosis plays a role in infectious diseases, but its regulatory mechanism in NS-related ALI remains unclear. The aim of this study is to investigate the mechanism of EMX2OS in promoting ferroptosis in ALI.MethodsThe expression level of EMX2OS in peripheral blood of patients with NS and its diagnostic value were detected by clinical samples. LPS-induced A549 cells were used to establish an ALI model. The targeting relationship between EMX2OS, miR-654-3p and AKT3 was verified by qRT-PCR, CCK-8, detection kit and dual-luciferase assays, and the cell viability and ferroptosis level were evaluated.ResultsEMX2OS was highly expressed in NS and served as a potential diagnostic marker. In LPS-induced lung injury model, high expression of EMX2OS decreased cell viability and enhanced ferroptosis. Silencing EMX2OS had the opposite effects. EMX2OS regulated cell viability and ferroptosis through miR-654-3p/AKT3 axis.ConclusionsThis study reveals for the first time that EMX2OS serves as a diagnostic marker for NS and promotes ferroptosis through miR-654-3p/AKT3 axis, thereby exacerbating lung injury. EMX2OS to regulate ferroptosis may become potential therapeutic strategies for lung injury.